2019
DOI: 10.1097/gox.0000000000002081
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Face and Head Movement in Infants with and without Craniofacial Microsomia: An Automatic Approach

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Constrained local neural fields (CLNF) [37] is used to track 2D facial landmarks. It is known that people tend to move their heads and faces when they make a transition from one affective state to others (e.g., neutral to positive affect state) [20], [21] and this information can be captured from head pose [38], [39]. Considering that, this work tracks head pose translation and rotation using CLNF [40].…”
Section: Methods a Motivation And Multimodal Facial Features Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Constrained local neural fields (CLNF) [37] is used to track 2D facial landmarks. It is known that people tend to move their heads and faces when they make a transition from one affective state to others (e.g., neutral to positive affect state) [20], [21] and this information can be captured from head pose [38], [39]. Considering that, this work tracks head pose translation and rotation using CLNF [40].…”
Section: Methods a Motivation And Multimodal Facial Features Trackingmentioning
confidence: 99%
“…There are some works on expressiveness as well. Such as Hammal et al [20], [21] examined facial expressiveness in infants with and without complex congenital conditions named craniofacial microsomia which could impair facial expressiveness; they reported that expressiveness varied between positive and negative affect. Neubauer et al [22] reported that oxytocin increases facial expressivity in both healthy and schizophrenia populations.…”
Section: Related Workmentioning
confidence: 99%
“…29 (While there were no differences in facial expressiveness between children with and without craniofacial microsomia when scored by observers, computer vision-based scoring identified less expressiveness in cases with microtia with mandibular hypoplasia and other associated features of CFM. 58,59 ) At follow-up between 36 and 42 months, cases (n = 92) and controls (n = 76) had average range cognitive and motor mean scores; however, children with CFM had 2 lower language subtest scores and 39% had an area of delay. 30 The second study series was based on a sample described in Werler et al of 230 case participants with HFM and 678 matched controls from 26 craniofacial centers in the United States and Canada.…”
Section: Psychosocial Experiencesmentioning
confidence: 99%